Extractive masculinities: Bringing gender back into microfinance - Smitha Radhakrishnan (economic sociology. perspectives and conversations, 2022)
When Mohammed Yunus won the Nobel Peace Prize in 2006, he drew global attention to the potential benefits of lending small amounts of money to impoverished women in cooperative groups. His work in Bangladesh, in cooperation with the Bangladesh Rural Advancement Committee (BRAC), had lowered vulnerabilities for women in rural areas to a large extent, and appeared to be a promising method for addressing global poverty (2014).
Keywords: 300